2013
DOI: 10.1105/tpc.112.108340
|View full text |Cite
|
Sign up to set email alerts
|

A DEAD Box RNA Helicase Is Critical for Pre-mRNA Splicing, Cold-Responsive Gene Regulation, and Cold Tolerance inArabidopsis   

Abstract: Cold stress resulting from chilling and freezing temperatures substantially reduces crop production worldwide. To identify genes critical for cold tolerance in plants, we screened Arabidopsis thaliana mutants for deregulated expression of a firefly luciferase reporter gene under the control of the C-REPEAT BINDING FACTOR2 (CBF2) promoter (CBF2:LUC). A regulator of CBF gene expression1 (rcf1-1) mutant that is hypersensitive to cold stress was chosen for in-depth characterization. RCF1 encodes a cold-inducible D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
141
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 66 publications
3
141
0
Order By: Relevance
“…The cold-inducible RNA helicase REGULA-TOR OF C-REPEAT BINDING FACTOR GENE EXPRESSION1 is essential for splicing and is important for cold-responsive gene expression and cold tolerance in Arabidopsis (Guan et al, 2013). PRMT5, a type II protein Arg methyltransferase that symmetrically dimethylates Arg side chains, also impacts splicing/AS in Arabidopsis.…”
Section: Function Of Sfs In Abiotic Stress Responsementioning
confidence: 99%
“…The cold-inducible RNA helicase REGULA-TOR OF C-REPEAT BINDING FACTOR GENE EXPRESSION1 is essential for splicing and is important for cold-responsive gene expression and cold tolerance in Arabidopsis (Guan et al, 2013). PRMT5, a type II protein Arg methyltransferase that symmetrically dimethylates Arg side chains, also impacts splicing/AS in Arabidopsis.…”
Section: Function Of Sfs In Abiotic Stress Responsementioning
confidence: 99%
“…In plants, DEADbox RNA helicases have been associated with diverse molecular functions such as siRNA-mediated gene silencing, premRNA splicing, chloroplast/mitochondrial intron splicing, nonsense-mediated mRNA decay, mRNA export, ribosome biogenesis and exon-junction complex functions. [11][12][13][14][15][16][17][18][19][20][21][22] Furthermore, it has been shown that these helicases play roles in Keywords: abiotic stress, Arabidopsis thaliana, DEAD-box RNA helicases, epigenetic gene silencing, nucleolus, RNAdirected DNA methylation Abbreviations: ABA, abscisic acid; STRS, STRESS RESPONSE SUPPRESSOR; RdDM, RNA-directed DNA methylation. various biological processes including abiotic stress responses.…”
mentioning
confidence: 99%
“…various biological processes including abiotic stress responses. 6,12,15,19,[23][24][25][26][27][28][29] To further explore the function of the STRS DEAD-box RNA helicases in regulating abiotic stress-responsive gene expression, we examined STRS sub-cellular localization.…”
mentioning
confidence: 99%
“…However, the DEVH-box helicase mutant, Athelps, had increased autophagy while the nucleoside phosphatase mutant did not. Combined with the important physiological roles that DEAD-box family helicases play in RNA mechanisms (Guan et al 2013;Tuteja et al 2014;Zhang et al 2014), as well as their RNA-binding and ATP hydrolysis ability ), I speculate that AtHELPS is involved in an RNautophagy-like process in plants.…”
Section: Discussionmentioning
confidence: 99%
“…AtHELPS seems to functions as a negative regulator during low potassium stress ). Other DEAD-box helicases have been implicated in a variety of physiological processes in plants including determination of cell fate, biotic and abiotic stress, gene silencing, and growth (Kobayashi et al 2007;Guan et al 2013;Gu et al 2014;Khan et al 2014;Tuteja et al 2014;Zhang et al 2014).…”
Section: A Devh-box Helicase Mutant Shows Increased Basal Autophagymentioning
confidence: 99%